Understanding information: interlocking dimensions and terminology - Cronin, Blaise (ACURIL [S.l.], 1993)
Describes practical information management. Notes that with sweeping economic liberalization, the emergence of free trading blocs and the progressive erosion of tariff and new tariff barriers, trade wars will be redefined as intelligence warfare. In a competitive market place, companies need to know whether, how, and under what conditions their rivals compete. One solution for small nations is joint initiatives and collective boot strapping. Makes suggestions for co-prosperity initiatives which could be piloted in the Caribbean.